Nightwatch : nightlife in the Tropical Rain Forest. (Pleasantville, N. Y : Reader's Digest Children's Books, 1999)
Nightwatch transport you deep into the jungle, to roam the forests as the animals do.
Keywords: Animals-Juvenile literature; Tropical Rain Forest-Juvenile literature